2020
DOI: 10.1016/j.cell.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Transcriptional Scanning in the Testis Modulates Gene Evolution Rates

Abstract: Highlights d Genes expressed in the testis have reduced germline mutation rates d Germline mutational signature is tuned by spermatogenesisgene expression levels d Genes not expressed during spermatogenesis are enriched for fast-evolving functions d A germline mutational signature generated by TCR follows a ''3 0 -pyrimidine rule''

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 105 publications
7
71
1
Order By: Relevance
“…Additionally, in our comparison of the spermatozoal DNA methylome to that of almost 6,000 somatic tissue samples, we showed that gene ontology terms enriched amongst hypermethylated CpG sites in sperm pointed repeatedly to transcriptional regulation. This is an intriguing finding considering that recent research has shown that high overall levels of transcription during spermatogenesis facilitate transcription-coupled DNA repair mechanisms through so-called "transcriptional scanning" [38]. Given that transcriptional regulation is an essential process for all cell-types, it is striking to observe sperm-specific DNA methylation patterns enriched in these processes.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, in our comparison of the spermatozoal DNA methylome to that of almost 6,000 somatic tissue samples, we showed that gene ontology terms enriched amongst hypermethylated CpG sites in sperm pointed repeatedly to transcriptional regulation. This is an intriguing finding considering that recent research has shown that high overall levels of transcription during spermatogenesis facilitate transcription-coupled DNA repair mechanisms through so-called "transcriptional scanning" [38]. Given that transcriptional regulation is an essential process for all cell-types, it is striking to observe sperm-specific DNA methylation patterns enriched in these processes.…”
Section: Discussionmentioning
confidence: 93%
“…At this stage, damage accumulation is spontaneous while damage dilution via proliferation is not supported in most cell types. During the process of fertilization or before/after it, this damage gets thoroughly checked, cleared and diluted by the transition to the "pro-stemness" state[78][79][80]100 . An example of such a "reset" function exists at fertilization in C. elegans where lysosomal functions in oocytes are enhanced by sperm-secreted hormones, allowing degradation of protein aggregates and protein homeostasis 101.…”
mentioning
confidence: 99%
“…Thus, a combination of cell growth, selection, and proliferation dilutes mild damage, in addition to the removal of damage through specialized detoxification, repair, excretion, preemption, and other approaches. These mechanisms together allow the cells to keep the damage in control 80.…”
mentioning
confidence: 99%
“…Due to the lack of evidence of domains or sequence motifs in Tex33, it's still hard to explain which gene replaces the Tex33 in vivo yet. Recent study implies redundant testis-specific genes may not be idle or useless to the male, because the initiation of vast gene expression can prevent germ cell's DNA mutation via transcription-coupled repair (TCR), in order to avoid hereditary of wrong DNA message to the offspring (Xia et al, 2020). Our study suggests that a testis-predominantly expressed genes Tex33 is not necessary to spermatogenesis and male fertility, we should focus on genes that are indispensable to male fertility.…”
Section: Discussionmentioning
confidence: 87%